Advancing our thinking in presence‐only and used‐available analysis. (14th March 2013) - Warton, David; Aarts, Geert
Summary: 1. The problems of analysing used‐available data and presence‐only data are equivalent, and this paper uses this equivalence as a platform for exploring opportunities for advancing analysis methodology. 2. We suggest some potential methodological advances in used‐available analysis, made possible via lessons learnt in the presence‐only literature, for example, using modern methods to improve predictive performance. We also consider the converse – potential advances in presence‐only analysis inspired by used‐available methodology. 3. Notwithstanding these potential advances in methodology, perhaps a greater opportunity is in advancing our thinking about how to apply a given method to a particular data set. 4. It is shown by example that strikingly different results can be achieved for a single data set by applying a given method of analysis in different ways – hence having chosen a method of analysis, the next step of working out how to apply it is critical to performance. 5. We review some key issues to consider in deciding how to apply an analysis method: apply the method in a manner that reflects the study design; consider data properties; and use diagnostic tools to assess how reasonable a given analysis is for the data at hand. Abstract : The important problems of analysing used‐available data and presence‐only data are equivalent, and this paper leverages this equivalence to propose advances in analysis methodology. But perhaps we should be thinking more about how best to apply a given method ‐ applying a method in different ways can give very different results.